DUALITAS PERAN SANTRI TAHFIZ PONDOK MODERN DARUL HIKMAH TAWANGSARI - Husnul Amira; Ayu Cintana; Mumtazah Al ‘Ilmah; M. Muntahibun Nafis; Salamah Noorhidayati (LPPM UMC, 2023)
The duality of the role of Tahfiz students in Indonesia is increasingly widespread with the existence of Islamic boarding schools, especially Tahfiz Islamic boarding schools, which are starting to integrate the Tahfiz program with formal schools. One of the interesting boarding schools for research is Pondok Modern Darul Hikmah which integrates the tahfiz program with formal schools while emphasizing the use of Arabic and English as languages ​​of daily communication. In this way, the tahfiz students of Pondok Modern Darul Hikmah have two important roles that must be carried out. From this research, researchers found that the dual role of Islamic boarding school students at Pondok Modern Darul Hikmah (as memorizers of the Qur'an as well as students) is indeed difficult, but they can carry it out with balance and full responsibility. Even though there are several factors that become obstacles, they can still get good academic grades without neglecting their memorization targets